Knowledge environments in universities - Meusburger, Peter (Hungarian Geographical Bulletin, 2015)
Talent, motivation, and wealth of ideas are not the only characteristics determining how successfully a scholar's research and academic career develops. What we academics call creative is never the result of individual action alone. Learning processes and research are situated in environments, organisational structures, and spatial relations. We cannot study scientific creativity by isolating scholars and their works from the social and historical milieu in which their actions are carried out. A stimulating environment and a talented individual must come together and interact before a creative process can occur. This article addresses four questions: What elements constitute a local knowledge environment? How can a local knowledge environment affect learning and research processes? How can one measure the impact of a knowledge environment and avoid the trap of determinism? What theoretical concepts can contribute to the analysis of knowledge environments and the explanation of their impact?